The kinematic relationships of ball release speed in elite female cricket pace bowlers - Feros, S. A.; Gerhardy, M. H.; Fyfe, J. J.; Dwyer, D. B. (International Journal of Sports Science & Coaching, 2024)
The ability of a pace bowler to deliver the cricket ball at faster speeds is linked with improved match performance as they require less deliveries to take a wicket and concede less runs per wicket taken. The aim of this study was to explore the relationship between ball release speed and selected pace bowling kinematics in 19 elite female pace bowlers. Participants bowled 18 match-intensity deliveries indoors from a full run-up. Peak ball release speed and three-dimensional pace bowling kinematic data were extracted from six deliveries that met specific selection criteria. Linear and non-linear relationships were assessed between ball release speed and selected pace bowling kinematics. Ball release speed was associated linearly with pelvis orientation at back foot contact (r2 = 0.34, p = 0.048) and non-linearly with thoraco-pelvic lateral flexion at front foot flat (r2 = 0.69, p < 0.001). Compared to their slower counterparts, faster elite female pace bowlers were more side-on at back foot contact and more upright in the frontal plane at front foot flat. A side-on pelvis orientation at back foot landing is likely to permit greater whole-body angular momentum in the transverse plane of motion. A more upright trunk orientation at front foot flat may be indicative of delayed onset of trunk flexion and representative of optimal segmental sequencing to maximise ball release speed. This knowledge is likely to be useful in the coaching and development of female pace bowlers for the purposes of enhancing ball release speed and therefore match performance.